Consultants risk : an investigation into the impact of discounted professional fees on the risk exposure of civil and structural engineering services consultants in South Africa - Okonkwo, Patrick Nwabueze (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2014.